The Dynamics of Leadership, Supervision, and Punishment in Improving Job Satisfaction: Dinamika Kepemimpinan, Pengawasan, dan Punishment dalam Meningkatkan Kepuasan Kerja - Hidayati, Siti Nur; Kusuma, Kumara Adji; Andriani, Dewi; Abadiyah, Rifdah (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: In a competitive industrial environment, understanding factors that enhance job satisfaction is essential for fostering a motivated workforce. Specific Background: Existing literature primarily addresses leadership and supervision but often neglects the impact of punishment styles on employee morale. Knowledge Gap: This study investigates the interplay between transformational leadership, supervisory practices, and punishment styles in shaping job satisfaction among employees of PT. Young Tree Industries. Aims: Employing a quantitative survey approach, the research aims to evaluate these factors' individual and collective effects on employee satisfaction. Results: Data were collected from 384 employees through a structured questionnaire, analyzed using SPSS software. The findings reveal that transformational leadership, supervision, and punishment styles significantly positively influence job satisfaction. Transformational leadership emerged as the most impactful variable. Novelty: This study contributes to the literature by highlighting the importance of both leadership and punishment styles in enhancing employee job satisfaction, thus providing a comprehensive view of managerial impacts in the workplace. Implications: The results suggest that organizations should prioritize transformational leadership development and effective supervision while addressing punishment methods to improve employee satisfaction and, consequently, overall productivity. Highlights: Leadership Impact: Transformational leadership boosts employee job satisfaction significantly. Supervision Role: Effective supervision enhances overall job satisfaction among employees. Punishment Effects: Appropriate punishment styles improve workplace job satisfaction. Keywords: employee job satisfaction, transformational leadership, supervision, punishment styles, quantitative research